Changes in the central nervous system of prematurely born children - Modrzejewska, Monika; Kot, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Preterm birth adversely affects the maturation of the central nervous system, including the process of white matter myelination, still incomplete at this stage. Prematurity is also a risk factor for the future visual impairment. Decreased visual acuity in premature infants observed during their development, may be caused by both retinopathy of prematurity and the damage to the central nervous system. Owing to the development of new magnetic resonance imaging techniques such as diffusion imaging and diffusion tensor imaging, a detailed evaluation of changes to the cerebral white matter microstructure is now possible. As postulated in the newly published literature, ocular pathologies in premature infants may be related to abnormalities within the corpus callosum. Modern imaging techniques prove to be of the essencewhen facing diagnostic challenges in premature infants presenting with visual disturbances.